The Use of Swearing Words of Young Multicultural Students: A Sociolinguistics Study - Shela Setyaningtias; Eko Heriyanto; Ahmad Muhid (English Language and Education Spectrum, 2023)
In today’s modern era, it has become a common phenomenon to hear swearing words that are often spoken by people around us, as well as UNAKI students who live in dormitories and come from various regions. Lack of education about the use of swearing words, makes them quite often use these swearing words in daily conversation with their friends because they are young and vulnerable. Therefore, educating them about the dangers of swearing words is very much needed for the sake of the better quality of the younger generation. The aim is to analyze the use of swearing words that are often spoken by UNAKI students living in dormitories and to analyze the function of swearing words used by UNAKI students living in dormitories. This study uses a descriptive qualitative research design. The population in this study was all students who lived in dormitories. 20 teenagers were sampled with 5 people from each area consisting of Lampung, Kalimantan, Medan, and Papua. The research data were obtained by observation, interviews, note-taking, and simak methods. The result of this research is that there are five types of swearing words used by UNAKI students who live in dormitories: obscenity, abusive, blasphemy, expletive, and humorous. They use swearing words to express their indescribable feelings such as anger, annoyance, and show intimacy in a friendship relationship. The conclusion is that the swearing words used by UNAKI students who live in dormitories have five types and three functions.